1993
DOI: 10.1093/nar/21.24.5727
|View full text |Cite
|
Sign up to set email alerts
|

Heterodimeric DNA-binding dyes designed for energy transfer: synthesis and spectroscopic properties

Abstract: Heterodimeric dyes are described which bind tightly to double-stranded (dsDNA) with large fluorescence enhancements. These dyes are designed to exploit energy transfer between donor and acceptor chromophores to tune the separation between excitation and emission wavelengths. The dyes described here absorb strongly at the 488 nm argon ion line, but emit at different wavelengths, and can be applied to multiplex detection of various targets. The chromophores in these dyes, a thiazole orange-thiazole blue heterodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 19 publications
1
37
0
Order By: Relevance
“…Thus, fluorescence resonance ET has been used extensively as a spectroscopic ruler for biological structures (13), and ET-coupled tandem phycobiliprotein conjugates have found wide application as unique fluorescent labels (14). Earlier, we showed that polycationic heterodimeric fluorophores that exploit ET and that have high affinities for double-stranded DNA offer advantages over monomeric fluorophores in multiplex fluorescence-labeling applications (15)(16)(17). We show here that the ET primers are markedly superior to single dye-labeled primers in DNA sequencing, and we anticipate that they will find broad use in multiplex PCR-based mapping and sizing protocols.…”
mentioning
confidence: 99%
“…Thus, fluorescence resonance ET has been used extensively as a spectroscopic ruler for biological structures (13), and ET-coupled tandem phycobiliprotein conjugates have found wide application as unique fluorescent labels (14). Earlier, we showed that polycationic heterodimeric fluorophores that exploit ET and that have high affinities for double-stranded DNA offer advantages over monomeric fluorophores in multiplex fluorescence-labeling applications (15)(16)(17). We show here that the ET primers are markedly superior to single dye-labeled primers in DNA sequencing, and we anticipate that they will find broad use in multiplex PCR-based mapping and sizing protocols.…”
mentioning
confidence: 99%
“…For experiments using fluorescent intercalating dye for detection, 500-bp PvuII fragments from plasmids pBL4 and pBL6 (8) were used; pBL4 and pBL6 contain four and six NGAAN repeats, respectively. An aliquot of dimeric intercalating fluorescent dye (either TOTO (22) or TOTAB (15,16)) was added to the DNA-protein mixture at a DNA base pair to dye molar ratio of 40:1, and the reaction mixture incubated in the dark at room temperature for 30 min. After electrophoresis, gels with radiolabeled complexes were dried and scanned using a Molecular Dynamics PhosphorImager.…”
Section: Methodsmentioning
confidence: 99%
“…To measure the absolute quantities of protein and DNA in each complex, we developed a two-color mobility shift fluorescence assay with a mutant HSF DT engineered for site-specific labeling with fluorescein and target DNA labeled with thiazole orange-thiazole blue heterodimer (TOTAB), an "energy transfer" dye (15,16). A technical difficulty was encountered in this work.…”
mentioning
confidence: 99%
“…Interest in nonradioactive DNA stains that are stable under gel electrophoretic conditions has led to the synthesis and characterization of a family of homo-and heterodimeric DNA-binding dyes (1)(2)(3). Organic fluorescent probes (FPs) are, as a rule, polycyclic aromatic cations with the planar structure capable of incorporating (intercalating) between the planes of the DNA bases, pulling apart these planes and changing the structure of nucleic acids.…”
Section: Introductionmentioning
confidence: 99%
“…Bis-intercalating TOTO-1 dyes have a weak fluorescence in the free state, but they sharply (more than 1000 times) increase fluorescence due to binding with DNA (4) and, therefore, they are widely used in biological, medical and drug development areas as fluorescent labels and probes (8)(9)(10)(11)(12)(13)(14)(15). They found also applications in genetic studies and modern diagnostic methods (1)(2)(3), for examples, in the case of the polymerase chain reaction for cancer diagnostics at early stages of the disease; for diagnostics of infection diseases (1)(2)(3)(4), including AIDS; for the identification of DNA samples in criminal law (16,17); flow cytometry (18), DNA sequencing (19,20) and quantification of nucleic acids in capillary and gel electrophoresis (21)(22)(23). Besides, they are commonly applied to lasers (24), electronics (25), nonlinear optics (26) and solar cells (27).…”
Section: Introductionmentioning
confidence: 99%